Data for paper 'Modelling alternating current effects in a submerged arc furnace' - Luckins, E; Oliver, J; Please, C; Sloman, B M; Valderhaug, A; Van Gorder, R (University of Oxford, 2022)
The attached files contain the data for the paper 'Modelling alternating current effects in a submerged arc furnace' by Ellen Luckins, James Oliver, Colin Please, Benjamin Sloman, Aasgeir Valderhaug and Robert Van Gorder, accepted for publication in the IMA Journal of Applied Mathematics (May 2022). See the READ ME file for a description of the data.